Effect of dengue infection on liver profile and hematological parameters - Muthalibu Muhammed Hunais; Shaheed Shiffana; Walawe Gamage Nimalka Udayangani (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2024)
Dengue fever is endemic in Sri Lanka. Liver damage is common in dengue fever. Understanding the pattern change of the liver profile and haematological parameters is crucial for managing dengue patients and minimising liver damage. The purpose of this study was to determine the pattern change in liver profile and the haematological parameters of dengue patients. Sixty apparently healthy volunteers and 169 acute dengue patients aged 20 or older had their blood samples examined. Liver enzymes, albumin, protein, bilirubin, white blood cell count, platelet count, haematocrit, and haemoglobin were measured. There was an increase in aspartate aminotransferase (105.6 IU/L), alanine aminotransferase (82.6 IU/L), and gamma-glutamyl transferase (68.9 IU/L), which were 3.4, 3.9, and 3.2-fold higher, respectively, than those of the control group, suggesting liver injury. Eighty-four percent of patients had raised levels of aspartate aminotransferase, and 74% of patients had elevated levels of alanine aminotransferase, indicating the prominence of aspartate aminotransferase over alanine aminotransferase. The presence of a positive correlation between the levels of aspartate aminotransferase and alanine aminotransferase indicates that the elevation of enzymes is primarily due to a single cause, liver injury. White blood cells and platelet counts were significantly lower. Platelet count demonstrated a negative correlation with both haematocrit and haemoglobin in dengue patients. In conclusion, aspartate aminotransferase was identified as the most significant marker of dengue-associated liver injury, followed by alanine aminotransferase. Low platelet and white blood cell counts were the major unfavourable changes in dengue patients' haematological characteristics.